Diversity of Astroglial Effects on Aging- and Experience-Related Cortical Metaplasticity - Lalo, Ulyana; Bogdanov, Alexander; Pankratov, Yuriy (Frontiers in Molecular Neuroscience, 2018)
Activity-dependent regulation of synaptic plasticity, or metaplasticity, plays a key role in the adaptation of neuronal networks to physiological and biochemical changes in ageing brain. There is a growing evidence that experience-related alterations in the mechanisms of synaptic plasticity can underlie beneficial effects of physical exercise and caloric restriction on brain health and cognition. Astrocytes, which form neuro-vascular interface and can modulate synaptic plasticity by release of gliotransmitters, attract an increasing attention as important element of brain metaplasticity. We investigated the age- and experience-related alterations in astroglial calcium signalling and stimulus-dependence of long-term synaptic plasticity in the neocortex of mice exposed to the mild caloric restriction (CR) and environmental enrichment (EE) which included ad libitum physical exercise. We found out that astrocytic Ca2+-signalling underwent considerable age-related decline but EE and CR enhanced astroglial signalling, in particular mediated by noradrenaline and endocannabinoid receptors. The release of ATP and D-Serine from astrocytes followed the same trends of age-related declined and EE-induced increase. Our data also showed that astrocyte-derived ATP and D-Serine can have diverse effects on the threshold and magnitude of long-term changes in the strength of neocortical synapses; these effects were age-dependent. The CR- and EE-induced enhancement of astroglial Ca2+-signalling had more stronger effect on synaptic plasticity in the old (14-18 months) than in the young (2-5 months) wild-type mice. The effects of CR and EE on synaptic plasticity were significantly altered in both young and aged dnSNARE mice. Combined, our data suggest astrocyte-neuron interactions are important for dynamic regulation of cortical synaptic plasticity. This interaction can significantly decline with ageing and thus contributes to the age-related cognitive impairment. On another hand, experience-related increase in the astroglial Ca2+-signalling can ameliorate the age-related decline.